PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PICTURE QUESTION CARD TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN IPAS SISWA KELAS III SD - Ainur Lailatul Hamidah; Yulina Ismiyanti (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2026)
This research aims to analyze the effectiveness of the Problem Based Learning (PBL) model combined with Picture Question Card (PQC) media in improving the critical thinking skills of class III students in IPAS learning. The research uses a quantitative approach with one group pretest-posttest pre-experimental design. The research subject consists of 28 students of SD Negeri Karangroto 04. Critical thinking ability is measured through a description test based on critical thinking indicators. The data obtained was analyzed using the Wilcoxon Signed Rank test to determine the differences before and after treatment. The research results show that there is a significant improvement after the implementation of the PBL model with the help of PQC media. The average student score increased from 68 during the pretest to 82 during the posttest. The results of statistical analysis showed a significance value of less than 0.05 which identified a meaningful influence. This finding shows that the integration of PBL with visual media based on question cards is effective in developing critical thinking skills of elementary school students in IPAS learning.